2017
DOI: 10.1039/c6cp07505c
|View full text |Cite
|
Sign up to set email alerts
|

Band gap opening in stanene induced by patterned B–N doping

Abstract: Abstract:Stanene is a quantum spin hall insulator and a promising material for electronic and optoelectronic devices. Density functional theory (DFT) calculations are performed to study the band gap opening in stanene by elemental mono-(B, N) and co-doping (B-N). Different patterned B-N co-doping is studied to change the electronic properties in stanene. A patterned B-N co-doping opens the band gap in stanene and the semiconducting nature persists with strain. Molecular dynamics (MD) simulations are performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 95 publications
(143 reference statements)
8
36
0
Order By: Relevance
“…On applying transverse electric field, half‐metallic states could be induced in nanoribbons, which has promising prospects in magnetic control and spintronics . In a recent study, interaction of various gases with stanene was investigated by Garg et al where the author found that stanene gas systems show Rashba type spin‐splitting, which is very promising for spintronics applications …”
Section: Unique Properties Of Elemental 2d Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…On applying transverse electric field, half‐metallic states could be induced in nanoribbons, which has promising prospects in magnetic control and spintronics . In a recent study, interaction of various gases with stanene was investigated by Garg et al where the author found that stanene gas systems show Rashba type spin‐splitting, which is very promising for spintronics applications …”
Section: Unique Properties Of Elemental 2d Materialsmentioning
confidence: 99%
“…Luo et al studied doping of B and N in phagraphene NRs and predicted that while B‐doping removed/changed the bandgap depending on doping position, N or BN doping increased the bandgap . Garg et al patterned stanene with BN doping and predicted a bandgap opening of ≈0.22 eV, and a semiconducting behavior sustained under applied strain …”
Section: Modulation Of Electronic Bandgap In 2d Materialsmentioning
confidence: 99%
See 3 more Smart Citations